Development of Flip Book-Based Cooperative Training Module to Enhance The Creative Character of Cooperative Administrators - Jayadi, Ahmad; Ratumbuysang, Monry Fraick Nicky Gillian; Satrio, Adrie; Mansur, Hamsi (FKIP ULM, 2024)
Cooperatives play a key role in supporting the growth and progress of micro, small, and medium enterprises (MSMEs) in various economic sectors. Training can be done to develop the quality of human resources, including training and developing the creative way of thinking of cooperative administrators. This research aims to produce a flip book-based cooperative training module to improve the creative character of cooperative administrators. The research method used is research and development. The modified model used is the ADDIE design. Evaluation by experts and individual trials of the training module resulted in recommendations for revision, receiving a rating of